9w+6-13=9w+12-19

Simple and best practice solution for 9w+6-13=9w+12-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9w+6-13=9w+12-19 equation:


Simplifying
9w + 6 + -13 = 9w + 12 + -19

Reorder the terms:
6 + -13 + 9w = 9w + 12 + -19

Combine like terms: 6 + -13 = -7
-7 + 9w = 9w + 12 + -19

Reorder the terms:
-7 + 9w = 12 + -19 + 9w

Combine like terms: 12 + -19 = -7
-7 + 9w = -7 + 9w

Add '7' to each side of the equation.
-7 + 7 + 9w = -7 + 7 + 9w

Combine like terms: -7 + 7 = 0
0 + 9w = -7 + 7 + 9w
9w = -7 + 7 + 9w

Combine like terms: -7 + 7 = 0
9w = 0 + 9w
9w = 9w

Add '-9w' to each side of the equation.
9w + -9w = 9w + -9w

Combine like terms: 9w + -9w = 0
0 = 9w + -9w

Combine like terms: 9w + -9w = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 1/5(t-9)=-7 | | 1+2-x=3+x+4 | | 5x+20=-3(-4+x) | | -66=6a | | 5y+1=7y-1 | | -7(7-5x)=27x | | 3(4x-6)=12x | | -90=5k-5(2+3k) | | 4+2x=5x-8 | | Logx+log(x-2)=0 | | 5.2a+11=68.2 | | 2m+4=8m-1 | | 4x-8=8+6 | | 5y+7=7y-1 | | 4x+3y+2z=15 | | 5x+4=6+5x | | x+3y+3z=16 | | 1+x+4=2+x+3 | | 4(6-3v)=96 | | 12m+5n-3m+10n= | | 160+.15m=241 | | 7x+117=-6x | | log[2]3x-6=4 | | -6x-3=3-6y | | 7x-35+3=6x-42 | | (x-6)-7=-3 | | 12p+19q+p-6q-3p= | | 1+x+2=3+x+4 | | 4(x+2)=30+3x | | X^2lnx-4lnx=0 | | 6a=80-4d | | 8x+10=8x-9 |

Equations solver categories